Changes in the Diagnosis of Stroke and Cardiovascular Conditions in Primary Care During the First 2 COVID-19 Waves in the Netherlands. (8th February 2022) - Velek, Premysl; Splinter, Marije J.; Ikram, M. Kamran; Ikram, M. Arfan; Leening, Maarten J.G.; van der Lei, Johan; olde Hartman, Tim; Peters, Lilian L.; Tange, Huibert; Rutten, Frans H.; van Weert, Henk; Wolters, Frank J.; et al.
Abstract : Background and Objectives: Although there is evidence of disruption in acute cerebrovascular and cardiovascular care during the coronavirus disease 2019 (COVID-19) pandemic, its downstream effect in primary care is less clear. We investigated how the pandemic affected utilization of cerebrovascular and cardiovascular care in general practices (GPs) and determined changes in GP-recorded diagnoses of selected cerebrovascular and cardiovascular outcomes. Methods: From electronic health records of 166, 929 primary care patients aged 30 or over within the Rotterdam region, the Netherlands, we extracted the number of consultations related to cerebrovascular and cardiovascular care, and first diagnoses of selected cerebrovascular and cardiovascular risk factors (hypertension, diabetes, lipid disorders), conditions, and events (angina, atrial fibrillation, TIA, myocardial infarction, stroke). We quantified changes in those outcomes during the first COVID-19 wave (March–May 2020) and thereafter (June–December 2020) by comparing them to the same period in 2016–2019. We also estimated the number of potentially missed diagnoses for each outcome. Results: The number of GP consultations related to cerebrovascular and cardiovascular care declined by 38% (0.62, 95% confidence interval 0.56–0.68) during the first wave, as compared to expected counts based on prepandemic levels. Substantial declines in the number of new diagnoses were observed for cerebrovascular events: 37% for TIA (0.63, 0.41–0.96) and 29% for stroke (0.71, 0.59–0.84), while no significant changes were observed for cardiovascular events (myocardial infarction [0.91, 0.74–1.14], angina [0.77, 0.48–1.25]). The counts across individual diagnoses recovered following June 2020, but the number of GP consultations related to cerebrovascular and cardiovascular care remained lower than expected throughout the June to December period (0.93, 0.88–0.98). Discussion: While new diagnoses of acute cardiovascular events remained stable during the COVID-19 pandemic, diagnoses of cerebrovascular events declined substantially compared to prepandemic levels, possibly due to incorrect perception of risk by patients. These findings emphasize the need to improve symptom recognition of cerebrovascular events among the general public and to encourage urgent presentation despite any physical distancing measures.